Ultrathin Ruddlesden–Popper Perovskite Heterojunction for Sensitive Photodetection. Issue 39 (7th August 2019) - Fu, Qundong; Wang, Xiaolei; Liu, Fucai; Dong, Yuxin; Liu, Zirui; Zheng, Shoujun; Chaturvedi, Apoorva; Zhou, Jiadong; Hu, Peng; Zhu, Zhuqing; Bo, Fang; Long, Yi; et al.
Abstract: Thanks to their unique optical and electric properties, 2D materials have attracted a lot of interest for optoelectronic applications. Here, the emerging 2D materials, organic–inorganic hybrid perovskites with van der Waals interlayer interaction (Ruddlesden–Popper perovskites), are synthesized and characterized. Photodetectors based on the few‐layer Ruddlesden–Popper perovskite show good photoresponsivity as well as good detectivity. In order to further improve the photoresponse performance, 2D MoS2 is chosen to construct the perovskite–MoS2 heterojunction. The performance of the hybrid photodetector is largely improved with 6 and 2 orders of magnitude enhancement for photoresponsivity (10 4 A W −1 ) and detectivity (4 × 10 10 Jones), respectively, which demonstrates the facile charge separation at the interface between perovskite and MoS2 . Furthermore, the contribution of back gate tuning is proved with a greatly reduced dark current. The results demonstrated here will open up a new field for the investigation of 2D perovskites for optoelectronic applications. Abstract : The hybridization of two semiconductors to form a heterojunction has improved photoresponse performance owing to the facile charge separation at the interface. Here, a 2D Ruddlesden–Popper perovskite is hybridized with 2D MoS2 to construct heterojunction photodetectors, which exhibit superior performance with ≈6 and 2 orders of magnitude improvement of photoresponsivity and detectivity, respectively, compared with pure Ruddlesden–Popper perovskite photodetectors.